Genomic alterations and precise medicine of esophageal squamous cell carcinoma - Qionghua Cui, BS; Chen Wu, MD, PhD; Dongxin Lin, MD (Journal of Bio-X Research, 2018)
Abstract. Human cancer is a complex disease caused by the interaction of multiple genes and environmental factors. It is known that environmental factors such as smoking, drinking, and food carcinogens are implicated in the development of certain types of cancer including esophageal squamous cell carcinoma (ESCC). However, only a small portion of exposed individuals finally developed cancer, indicating that genetic makeup also plays an important role in the tumorigenesis. Genome-wide association studies (GWAS) have found numerous susceptible genes or loci for cancers, providing new ideas and directions for precision prevention and treatment of cancers. With the advances in the field of next-generation sequencing (NGS), the genomic landscapes of many types of human cancer have comprehensively been characterized. Here, we review the progresses of GWAS and NGS in revealing genomic variations of ESCC, one of the most common cancers in China, and discuss the potential applications of these results in precision medicine of ESCC.